2018
DOI: 10.1002/aoc.4332
|View full text |Cite
|
Sign up to set email alerts
|

Design and Preparation of Poly‐Selenides: Easily Fabricated and Efficient Organoselenium Materials for Heavy Metal Removing and Recycling

Abstract: Reaction of 1,4-bis(chloromethyl)benzene with the in situ-generated NaHSe afforded a facile fabrication method of poly-selenide, a novel organoselenium material which was found to be efficient for heavy metal removing and recycling. The material could grab transition metals from their aqueous solutions and release them in HNO 3 . After treating with aqueous Na 2 SO 3 , the polymer could be refreshed and reused. It could absorb heavier Pb even than its own weight from high concentration solutions, and remove al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…20 However, the polyselenide synthetic conditions are usually incompatible with the enzymatic reaction conditions. 41,42 Therefore, we explored enzymatic systems. Cystathionine-β-lyase is a PLP-dependent enzyme that catalyzes the L-cystathionine to L-homocysteine transformation.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 However, the polyselenide synthetic conditions are usually incompatible with the enzymatic reaction conditions. 41,42 Therefore, we explored enzymatic systems. Cystathionine-β-lyase is a PLP-dependent enzyme that catalyzes the L-cystathionine to L-homocysteine transformation.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Our recent study on EanB catalysis indicated that inorganic polysulfides serve as the direct sulfur source, suggesting that polyselenide might share a similar function . However, the polyselenide synthetic conditions are usually incompatible with the enzymatic reaction conditions. , Therefore, we explored enzymatic systems. Cystathionine-β-lyase is a PLP-dependent enzyme that catalyzes the l -cystathionine to l -homocysteine transformation .…”
Section: Resultsmentioning
confidence: 99%
“…To overcome these limitations, preliminary separation and preconcentration processes become urgent steps that are needed before the direct measurement, especially in the presence of low concentrations of target ions. To date, numerous methods including solid phase extraction (SPE), [13][14][15][16][17][18] cloud point extraction (CPE), 19 otation, 20 and liquidliquid extraction (LLE) 21 have been designed for the separation and/or preconcentration of the heavy metal ions. Due to the high extraction efficiency, and rapid phase separation, the SPE has been widely applied as the preconcentration technique.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations on selenium chemistry have boomed during the past decade. The selenium-containing compounds/materials have been widely employed in a variety of industrial fields, such as organic synthesis, pharmaceutical industry, , fine chemical production, food industry, and even wastewater treatment. , Some organoselenium compounds have been found to be of relatively low toxicity and even nontoxic; e.g., the acutely lethal dose (LD50) of ebselen in rats treated intraperitoneally is 400 μmol/kg, while that for diphenyl diselenide is as high as 1200 μmol/kg . In comparison with transition metals, selenium as a necessary trace element for human beings can be metabolized by the body .…”
Section: Introductionmentioning
confidence: 99%